ANALISIS KONTRIBUSI PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA YOGYAKARTA TAHUN 2017-2021 - Ainun Hertikasari; Fadhla Khanifa; Amiroh Nabila Salsabil (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
The Special Region of Yogyakarta is a province in Indonesia that is often known as a student city and a cultural city. The existing tourism potential, of course, greatly contributes to increasing Regional Original Revenue revenue. Based on data from statistics from the Special Region of Yogyakarta Province, the number of hotels in 2020 was 172 star-rated hotels, while non-star hotels were 1,951. Restaurants in 2020 were 1,002 and restaurants were 1,007 in 2020 in the Special Region of Yogyakarta. This study examines the Analysis of the Contribution of Hotel Tax and Restaurant Tax to the Original Revenue of the Yogyakarta City Government in 2017-2021. This research was conducted on the Yogyakarta City Government with a period of 2017 – 2021. Research data collection is carried out by data collection methods, including: Documentation and Literature Research. The analysis tools used are hotel tax contribution analysis and restaurant tax. How much contribution does hotel tax and restaurant tax give to local revenue in the Yogyakarta city government in 2017-2021. Hotel Tax contributed to PAD in 2017 0.19%. In 2018, the contribution of Hotel Tax was 0.22%. In 2019, the contribution of Hotel Tax still increased to 0.23%. But in 2020 during the pandemic, hotel taxes decreased to 0.13%. In 2021, the decrease occurred in the Hotel Tax of 0.11%. The restaurant tax in 2017 was 0.06% then in 2018 it increased to 0.07%. In 2019, it increased again to 0.09%. Then in 2020 it decreased to 0.07%. And in 2021 there was no increase or decrease, which remained at 0.07%.